Survival after lobectomy versus sub-lobar resection in elderly with stage I NSCLC: a meta-analysis - Siyuan Dong; Steven A. Roberts; Shuang Chen; Xinwen Zhong; Shize Yang; Xiaohan Qu; Shun Xu (BMC Surgery, 2019)
Abstract Background We present a critical comparison of lobectomy and sub-lobar resection in elderly patients with early stage non-small cell lung cancer using meta-analytical techniques. Methods A literature search was conducted between the period of December 1997 to March 2019 to identify the comparative studies evaluating 1-, 3-, and 5-year survival rates. The pooled odds ratios (OR) and the 95% confidence intervals (95% CI) were calculated with either the fixed or random effect models, respectively. Results Six retrospective studies are included in our meta-analysis for a total of 1205 patients. 843 of the individuals were treated with lobectomy, while 362 were treated with sub-lobar resection. We found no significant difference between the lobectomy and the sub-lobar resection in either of the 1-, 3-, or 5-year survival rates. Conclusions This study suggests that in elderly individuals with stage I NSCLC, a sub-lobar resection is statistically equivalent to the lobectomy in terms of 1-, 3-, and 5-year survival rates. Further large-scale randomized studies are needed to confirm our results.